Pectinesterase extraction from papaya - Fayyaz, A.; Asbi, B.A.; Ghazali, H.M.; Che Man, Y.B.; Selamat, Jinap (Elsevier, 1993)
Pectinesterase (EC.3.1.1.11) was extracted from papaya fruit (Carica papaya L.) var. Exotica. Incubation time, pH and NaCl concentration influenced the extraction process of pectinesterase from papaya fruit. A maximum activity of 6·98 units/min ml was obtained with 2 m NaCl solution, pH 8, and at 5 h incubation time.